2011
DOI: 10.1111/j.1468-2494.2010.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a piroctone olamine/climbazol shampoo in comparison with a zinc pyrithione shampoo in subjects with moderate to severe dandruff

Abstract: Dandruff is a chronic scalp disorder characterized by scaling and itching. A successful anti-dandruff shampoo not only has to provide superior anti-dandruff relief to ensure patient compliance. It also needs to offer excellent cosmetic and hair conditioning benefits at the same time. In this study, the efficacy of a shampoo containing 0.5% piroctone olamine and 0.45% climbazole (shampoo 1) was compared with a widely available commercial shampoo containing 1% zinc pyrithione (shampoo 2). In vitro studies invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 16 publications
0
42
0
2
Order By: Relevance
“…Numerous clinical trials have been conducted to access the efficacy of antifungal treatments on different cohorts of patients with dandruff and seborrhoeic dermatitis . Ketoconazole is well‐documented to be an efficacious anti‐dandruff treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous clinical trials have been conducted to access the efficacy of antifungal treatments on different cohorts of patients with dandruff and seborrhoeic dermatitis . Ketoconazole is well‐documented to be an efficacious anti‐dandruff treatment .…”
Section: Discussionmentioning
confidence: 99%
“…The overall efficacy of antifungal shampoos in clinical trials has been compared in patients suffering from dandruff and seborrhoeic dermatitis . Comprehensive scalp microbiome comparisons have also been performed between cohorts of healthy individuals and dandruff/seborrhoeic dermatitis patients .…”
Section: Introductionmentioning
confidence: 99%
“…Climbazole is an imidazole antifungal agent. A non-steroidal cream containing piroctone olamine was reported to effectively treat SD by inhibiting the growth of Malassezia species7, and a shampoo containing piroctone olamine and climbazole effectively reduced dandruff by suppressing the growth of Malassezia 8. However, no study thus far has reported on an over-the-counter product containing piroctone olamine and climbazole for the treatment of facial SD.…”
Section: Introductionmentioning
confidence: 99%
“…2) Schmidt-Rose T et al, reported in their study that a combination of Piroctone Olamine (0.5%) and Climbazole (0.45%) proved to be equally effective on comparison with Zinc Pyrithione (1%) alone 28 .…”
Section:  Mechanism Of Actionmentioning
confidence: 99%